2014
DOI: 10.1371/journal.pone.0112516
|View full text |Cite
|
Sign up to set email alerts
|

CYLD Negatively Regulates Nontypeable Haemophilus influenzae-Induced IL-8 Expression via Phosphatase MKP-1-Dependent Inhibition of ERK

Abstract: Nontypeable Haemophilus influenzae (NTHi), a Gram-negative bacterium, is the primary cause of otitis media in children and the exacerbation of chronic obstructive pulmonary disease in adults. A hallmark of both diseases is an overactive inflammatory response, including the upregulation of chemokines, such as interleukin-8 (IL-8). An appropriate inflammatory response is essential for eradicating pathogens. However, excessive inflammation can cause host tissue damage. Therefore, expression of IL-8 must be tightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Glucocorticoids enhance NTHi-induced TLR2 upregulation via MKP1 phosphatase-dependent inhibition of p38 MAPK (21,24). MKP1 also seems to lead to reduced activation of the extracellular signal-regulated kinase (ERK) MAPK (39). Genome profiling revealed that the MKP1 encoding gene DUSP1 and p38 MAPK signaling are overexpressed in NTHi-infected cells.…”
Section: Resultsmentioning
confidence: 99%
“…Glucocorticoids enhance NTHi-induced TLR2 upregulation via MKP1 phosphatase-dependent inhibition of p38 MAPK (21,24). MKP1 also seems to lead to reduced activation of the extracellular signal-regulated kinase (ERK) MAPK (39). Genome profiling revealed that the MKP1 encoding gene DUSP1 and p38 MAPK signaling are overexpressed in NTHi-infected cells.…”
Section: Resultsmentioning
confidence: 99%
“…The FBXO11 is another important OM-related gene in mouse model mutation in FBXO11 that caused OM (Hardisty-Hughes et al, 2006). The deubiquitinase cylindromatosis (CYLD) gene expression involved in the suppression of the H. influenzae induced expression of pro-inflammatory chemokines (Wang et al, 2014). It has been suggested that PM weakens the host innate defense and obstructs the antibacterial peptides and proteins such as secretory leukocyte protease inhibitor and defensins (Chen et al, 2010(Chen et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…A series of evidence suggests that loss of CYLD expression is deeply associated with a wide variety of diseases, including malignant tumors, inflammatory diseases, infectious diseases, lung fibrosis, neural development, and cardiovascular dysfunction [79][80][81][82][83][84][85] . In this review, we described the clinical significance of CYLD, particularly focusing on the roles of CYLD as a critical regulator of hypoxia-mediated inflammation in GBM, which may affect the long-term efficacy of anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%